Strategic Digital Transformation: A Results-Driven Approach, 1st edition - Fenton, Alex (Routledge, 2020)
Emerging technologies are having a profound impact upon business as individuals and organisations increasingly embrace the benefits of the ‘always on’ attitude that digital technologies produce. The use of the web, apps, cloud storage, GPS and Internet-connected devices has transformed the way we live, learn, play and interact – yet how a business can fully benefit from this transformation is not always clear. In response, this book enables students and business leaders to take a strategic and sustainable approach to realising the value of digital technologies. It offers results-driven solutions that successfully transform organisations into data-driven, people-focused businesses capable of sustainably competing at a global level.